Targeting Wideband Circular Polarization: An Efficient 2×2 Sequentially-Phase-Fed Rotated Array Antenna - Mohammadi-Asl, Saeed; Nourinia, Javad; Ghobadi, Changiz; Majidzadeh, Maryain (Společnost pro radioelektronické inženýrství, 2018)
This paper outlines an efficient design of a wideband sequential-phase (SP) fed circularly polarized corner-truncated patch array antenna (CPCTPAA) with sequentially rotated (SR) array elements. The SP feed network is composed of a circular ring with an inner section of 270°. Four shorting strips are attached to the circular ring to the end of which corner-truncated patches (CTPs) are appended. Through the proposed feed structure, stable phase difference is attained at the end of the shorting strips which in turn ends in CP generation. Each array element of 2×2 CPCTPAA is a CTP printed on the top side of the FR4 substrate. On the backside, rectangular slots are removed from the ground plane to enhance the bandwidth characteristics of the proposed design. Moreover, suitable rectangular slots are embedded at the crossing points of CTPs and feed lines which instigate extra improvements in CPCTPAA performance. These amendments, all together, are deemed for achieving an efficient and cost-effective CPCTPAA design with smaller occupied implementation space. Simulation and experimental studies are conducted on a 70×70×1.6 mm3 prototype to evaluate performance of the proposed array antenna. Results are discussed in depth.
Keywords: Circular polarization; corner-truncated patches; rectangular shaped slots; sequential phase feed; wide Impedance bandwidth; wide CP bandwidth